Executive functions and processing speed in children with mild to borderline intellectual disabilities and externalizing behavior problems. Issue 4 (19th May 2017) - Schuiringa, Hilde; van Nieuwenhuijzen, Maroesjka; Orobio de Castro, Bram; Matthys, Walter
ABSTRACT: Several studies suggest impaired executive functions (EFs) in children with externalizing behavior problems and average intelligence (e.g., IQ > 85). Even though children with mild to borderline intellectual disabilities (MBID) are at higher risk of developing externalizing behavior problems compared to children with average intelligence, it is not yet clear if impaired EFs are also associated with the occurrence of externalizing behavior problems in children with MBID. In the current study, we therefore assessed three EF components (inhibition, cognitive flexibility, and working memory) as well as processing speed in children with MBID and externalizing behavior problems ( n  = 71) versus children with MBID with no such problems ( n  = 70). This was accomplished using a well-established computerized test battery. Even after IQ was controlled for, the children with MBID and externalizing behavior problems showed more impaired working memory performance. Differences for inhibition performance and processing speed were also found but less consistent across the tasks used to measure these aspects of EF. Cognitive flexibility was not more impaired in children with both MBID and externalizing behavior problems relative to children with MBID only. Our findings highlight working memory as a potential target to enhance the treatment of children with MBID and externalizing behavior problems.